Benefits of Emerging Markets Stocks and Foreign Exchange as Alternate Investment Assets and Their Causal Relation - Lee, Pooi Chie (2010)
This dissertation examines the benefit of investing in emerging markets and the use of foreign currency as an investment asset in a diversified portfolio for 9 developed and 6 emerging markets for the period July 2005 to June 2010. This is sub-divided into pre crisis (1 July 2005 to 30 June 2008) and post crisis (1 July 2008 to 30 June 2010) period in order to determine the impact of crisis to the asset’s risk-return trade-off and direction of causal relation between stock price and exchange rates. Our empirical results find that stocks from emerging markets outperform stocks from developed markets in a diversified portfolio due to its higher return, lower rate of increase in market volatility during crisis and lower correlation against assets from other countries. As for foreign currencies, we found negative correlation between Yen against US dollar and lower correlation between foreign currencies and US stock implies currency investment offer more risk-reducing potential than foreign stocks. Furthermore, we found evidence that investors prefer holding safe haven currencies like Yen and US dollar right after the outbreak of crisis while lessons learnt from previous financial crisis had made managed floating currencies to be more reliable in this recent crisis. While analysing the causal relation between stock return and exchange rates changes, we found significant causal relation from exchange rate to stock return in Japan and causal relation from stock return to exchange rate in Canada and Mexico to be consistent throughout the sample period. Our findings concluded that the linkages between the two asset classes cannot be completely explained by single theory as it vary across economies.